Plant Polypeptide Hormone Systemin Prefers Polyproline II Conformation in Solution - Dutta Chowdhury, Saikat; Lahiri, Ansuman (ACS omega, 2017)
Systemin, an 18 amino-acid-signaling peptide, was the first plant polypeptide hormone to be discovered. Earlier structural studies involving NMR spectroscopy indicated a lack of definite structure in solution while circular dichroism spectroscopy suggested the presence of left-handed polyproline II (PPII) conformation. Here, we report the results of molecular dynamics simulations of the peptide in explicit solvent with two different force fields, namely, ff99SBildn and ff99IDPs, both of which showed a large propensity for PPII-like conformations in spite of showing differing features for other conformational characteristics. More remarkably, the conformations with predicted chemical shifts that agreed better with the NMR observations had a larger than average PPII content, especially for the ff99IDPs force field. An independent docking calculation of the molecule with the putative receptor SR160 also retained this conformational preference for PPII structure. The results suggest PPII to be an important class of conformation for systemin which may have a role in its bioactivity.